Democratic Resilience and Institutional Reform in Post-Crisis Greece: A Political Analysis - Kyriakos Mitsotakis; Nikos Anastasiadis; Elira Dervishi; Jonida Shehu (JOCER: Journal of Civic Education Research, 2026)
This study examines democratic resilience and institutional reform in post-crisis Greece, addressing the limited integration of institutional performance, political legitimacy, and citizen trust within a unified analytical framework, focusing on the political transformations following the sovereign debt crisis. It analyzes how austerity measures, external pressures from European institutions, and domestic political dynamics have shaped democratic governance. Using a qualitative case study approach, the research employs document analysis and process tracing, drawing on policy documents, electoral data, and secondary literature to systematically assess to assess changes in political legitimacy, citizen trust, and institutional performance. The findings indicate that despite significant socio-economic disruptions, Greece has maintained democratic continuity, evidenced by sustained electoral processes and gradual institutional adaptation through sustained electoral participation and gradual institutional adaptation. However, these developments are constrained by persistent political polarization, fragile public trust, and limited administrative capacity, which undermine the depth and quality of democratic governance. The study also highlights the role of reforms aimed at enhancing transparency, accountability, and governance effectiveness. It argues that while formal democratic structures remain intact, the quality of democracy is constrained by tensions between externally driven reforms and domestic political legitimacy from both internal and external factors. The article contributes to debates on democratic resilience by proposing a multidimensional framework that integrates institutional reform, political legitimacy, and citizen engagement in crisis-affected democracies in crisis-affected states and offers insights for strengthening institutional frameworks in similar contexts.